COMPARISON OF A RAPID TEST WITH bPAG ELISA IN PREGNANCY DIAGNOSIS IN COWS - Dana, O. I.; Mukhtar, R. H.; Mohammed, M. O.; Dyary, H. O. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Early pregnancy detection is vital for properly managing livestock farms by re-inseminating nonpregnant females and minimizing the calving intervals. The present investigation was executed to compare a rapid test (Dairy Cow Pregnancy Test from Span Biotech Ltd. Shenzhen, China) with a commercial bPAG ELISA test (IDEXX®) for pregnancy diagnosis in non-descriptive cows. The study also aimed to elucidate if the rapid test could be an alternative method to ELISA in the field. Blood and urine samples were collected from 43 cows to measure the concentrations of bovine pregnancy-associated glycoproteins (bPAGs) in the blood samples and detect progesterone via the rapid test in the urine samples. Examining the genital tracts was achieved after slaughtering the cows to determine the uterus’ state, used as the reference standard for both tests. The results showed that the bPAG ELISA test was more accurate in pregnancy detection than the rapid test. However, there were no statistically significant differences (P > 0.05) between both methods’ results. We conclude that the rapid test can be a suitable alternative method to the bPAG ELISA test for diagnosing pregnancy in cows in field conditions.